Preliminary Study of Methyl Acetate Hydrolysis Using Reactive Dividing Wall Column - Herry Santoso (Seminar Nasional Teknik Kimia Kejuangan, 2015)
Methyl acetate is generated in a polyvinyl alcohol (PVA) plant as a byproduct with little industrial applications. One of the best considerations in reusing methyl acetate is to convert methyl acetate back to methanol and acetic acid, which serve as raw materials in PVA plant, using hydrolysis reaction. Methyl acetate hydrolysis using reactive dividing wall column is studied in this paper. Reactive dividing wall column incorporated reactive distillation column and separation column into a single column. Reactive dividing wall column is known for its prospective ability to reduce both capital and energy cost of a process. The aim of this study is to develop several design configurations of reactive dividing wall column for hydrolyzing methyl acetate to produce methanol and acetic acid. The process and economic performances of each design configuration are then evaluated and compared with the help of Aspen Plus process simulator in order to find the best reactive divided wall column design for methyl acetate hydrolysis.